Rapid emergency response mapping for the 2016 floods in Kelani river basin, Sri Lanka - Alahacoon, Niranga; Pani, Peejush; Matheswaran, Karthikeyan; Samansiri, Srimal; Amarnath, Giriraj (2016)
Paper presented at the 37th Asian Conference on Remote Sensing (ACRS): Promoting Spatial Data Infrastructure for Sustainable Economic Development, Colombo, Sri Lanka, 17-21 October 2016.